Prevalence of sub-optimal feeding practices and associated factors in very low birth weight infants admitted to the special care unit, Kawempe Hospital in Uganda - Amaniyo, Lucy; Dektar, Benbella; Nakibuuka, Victoria; Nankunda, Jolly; Opoka, Robert; Kiguli, Sarah (Frontiers in Pediatrics, 2025)
BackgroundOver 60% of Very Low Birth Weight (VLBW) infants worldwide are born in Sub-Saharan Africa and South Asia. VLBW infants are born nutritionally disadvantaged, as they are suddenly and prematurely moved from a nutrient-rich to a nutrient-deficient environment. Therefore, appropriate feeding during the early neonatal period is essential for the survival and growth of VLBW infants admitted to the special care unit of a Ugandan tertiary referral hospital.MethodsWe conducted a prospective cohort study among VLBW infants admitted to the Special Care Unit at Kawempe National referral hospital in Kampala, Uganda. Stable infants with no gross abnormalities or in need of resuscitation were recruited on day two of life and followed up until day seven or to discharge or death, whichever came first. Data were collected on socio-demographic and clinical characteristics, including birth weight initiation of enteral feeds, type of feeds received, and method of feeding. Observed feeding practices were compared to recommended VLBW feeding standards for appropriateness. Infants were followed up until day 7 of life. Logistic regression analysis was used to determine the factors associated with sub-optimal feeding.ResultsA total of 370 VLBW infants, with a mean gestational age of 32 weeks were enrolled. Overall, 333 (90%) had sub-optimal feeding and this was significantly associated with a sub-optimal rate of early weight change (growth velocity) [OR = 6.81, 95%, CI (2.74 to 16.97)]. Factors associated with sub-optimal feeding included: early initiation of enteral feeds [AOR = 11.03, 95%, CI (1.34 to 90.77)] and low scores on social support scale for the mother [AOR = 2.78, 95%, CI (1.14 to 6.82)].ConclusionsThere is a very high prevalence of sub-optimal feeding practices for VLBW infants in this population. This calls urgent need for improved feeding practices, including early enteral feeding. Future studies should explore the long terms effects of this early sub-optimal feeding practices on growth and development within the first 48 h, barring contraindications.